Oblique impact analysis on Kenaf (Hibiscus Cannabinus) and flax (Linum Usitatissimum) natural fiber sport cycling helmets - Mohd Na'im, Abdullah (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe